2016
DOI: 10.1111/1752-1688.12472
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Changes in Precipitation Amount and Distribution on Water Resources Studied Using a Model Rainwater Harvesting System

Abstract: Water supply reliability is expected to be affected by both precipitation amount and distribution changes under recent and future climate change. We compare historical (1951‐2010) changes in annual‐mean and annual‐maximum daily precipitation in the global set of station observations from Global Historical Climatology Network and climate models from the Inter‐Sectoral Impact Model Intercomparison Project (ISI‐MIP), and develop the study to 2011‐2099 for model projections under high radiative forcing scenario (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…In this context, Westra et al [33] analyzed the relationship between maximum daily rainfall and the global near-surface temperature, finding a positive relationship between both variables. Similarly, worldwide studies done by O'gorman [34] and Asadieh & Krakauer [35], found that the maximum daily precipitations are growing faster than the average annual precipitation, implying that rainfall intensity is generally increasing, which is similar to what Sarricolea & Martin-Vide [27] and Sarricolea et al [28] found in Chile, through a CI analysis. Therefore, the objective of this study was to characterize in time and space the behavior and concentration of daily and monthly rainfall in two climatic zones (arid-semiarid and humid-subhumid) of the country.…”
Section: Introductionsupporting
confidence: 67%
“…In this context, Westra et al [33] analyzed the relationship between maximum daily rainfall and the global near-surface temperature, finding a positive relationship between both variables. Similarly, worldwide studies done by O'gorman [34] and Asadieh & Krakauer [35], found that the maximum daily precipitations are growing faster than the average annual precipitation, implying that rainfall intensity is generally increasing, which is similar to what Sarricolea & Martin-Vide [27] and Sarricolea et al [28] found in Chile, through a CI analysis. Therefore, the objective of this study was to characterize in time and space the behavior and concentration of daily and monthly rainfall in two climatic zones (arid-semiarid and humid-subhumid) of the country.…”
Section: Introductionsupporting
confidence: 67%
“…Loss (t) is net amount of gain and loss of the reservoir resulting from precipitation and evaporation in time step t. Ev(t) is the evaporation height during the time step t, and x 0 , x 1 , x 2 and x 3 are constants that can be obtained by fitting Equation 15to the existing data. In cases where the evaporation loss is not considered in the formulations, Loss (t) is excluded from the Equation (11). In a hydropower reservoir operation, the objective is to obtain a set of releases from the reservoir (or a set of reservoir storage volumes) such that the power generation from the reservoir is maximum, or as close as possible to the installed capacity of the hydro-electric plant.…”
Section: Water-supply and Hydropower Reservoir Operationmentioning
confidence: 99%
“…RWHS can be defined as direct collection of rainwater from roof and other purpose-built catchments and the collection of sheet runoff from man-made ground or natural surface catchment and rock catchment for potable and non-potable uses. Studies on RWHS have been intensively carried out, since this system has several advantages for the environment and community [82][83][84][85][86][87][88][89][90][91]. Over the past four decades, the number of studies related to RWHS has increased exponentially as shown in Figure 3 based on a keyword 'RWHS' in Scopus database.…”
Section: Global Perspective Of Rwhsmentioning
confidence: 99%